ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN VOLUME PENJUALAN PADA UMKM AKAR KELAPA MPOK NINI OLEH-OLEH KHAS BETAWI DI BEKASI - Handayani, Dewi; Firmansyah, Ade (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to analyze marketing strategies to increase sales volume for MSMEs of Mpok Nini coconut roots, typical Betawi souvenirs located at the Damri Bus Terminal, Bekasi. This research is a qualitative type with a descriptive approach. Data collection techniques use interview, observation and documentation methods. The determination of informants was based on the owners and employees of the MSMEs of MPok Nini coconut roots as typical Betawi souvenirs, the buyers of the MSMEs of MSMEs with Mpok Nini coconut roots as typical Betawi souvenirs, and the determination of academic lecturer informants was selected based on the Business Administration course at the STIAMI Institute of Social Sciences and Management. The informants selected were 2 people from the UMKM mpok nini coconut roots for typical Betawi souvenirs, 2 buyers from UMKM mpok nini coconut roots for typical Betawi souvenirs, and 1 informant, an academic lecturer. Interview questions are based on the marketing mix of the 4P marketing strategy, namely Product, Price, Place, Promotion. Based on these dimensions, there are each indicator to be used as questions in interviews. The 4P marketing strategy has been implemented by MPOK Nini coconut root MSMEs, typical Betawi souvenirs, products that maintain excellence, prices at affordable selling prices, places available in marketplaces and offline stores, as well as promotions carried out through marketplace advertising. The obstacle in implementing a marketing strategy is the emergence of competitors selling the same product and similar packaging.